Epidemiological and molecular characteristics of meticillin-resistant Staphylococcus aureus in Turkey: A multicentre study. (September 2016) - Dündar, Devrim; Willke, Ayse; Sayan, Murat; Koc, Meliha Meric; Akan, Ozay Arıkan; Sumerkan, Bulent; Saltoglu, Nese; Yaman, Akgun; Ayaz, Celal; Koksal, Iftihar
Highlights: MRSA isolates from Turkey were mostly SCC mec type III and spa type t030. The community-associated (CA)-MRSA rate was low (0.7%) among Turkish MRSA isolates. The epidemiology of MRSA is changing rapidly. Definition of CA-MRSA is becoming more complicated. Combined use of epidemiological and genotypic methods is suggested. Abstract: The aim of this study was to investigate the epidemiological and molecular features of clinical meticillin-resistant Staphylococcus aureus (MRSA) isolates in Turkey. MRSA isolates were collected from six regions of Turkey. The mecA and nuc genes were detected by PCR. Antimicrobial susceptibilities were determined by the disk diffusion method. Staphylococcal cassette chromosome mec (SCC mec ) and staphylococcal protein A ( spa ) typing were performed by the sequencing method for 270 randomly selected MRSA isolates. The US Centers for Disease Control and Prevention (CDC) definition was used for epidemiological diagnosis of community-associated MRSA (CA-MRSA). Resistance rates of MRSA to ciprofloxacin, gentamicin, clindamycin, erythromycin, rifampicin, trimethoprim/sulfamethoxazole and tetracycline were 93.4%, 81.2%, 38.5%, 57.8%, 93.9%, 1.1% and 93.1%, respectively. The most frequent SCC mec type was SCC mec III (91.1%). SCC mec type IV was found in 5.2% of the isolates. The most frequent spa type was t030 (81.1%). Five isolates were CA-MRSA if only the epidemiological definition was used (5/725; 0.7%). Two isolates were defined as CA-MRSA both by epidemiological features and SCC mec typing (2/270; 0.7%). Of 14 SCC mec type IV isolates, 12 were not defined as CA-MRSA by epidemiological features. In conclusion, this is the most comprehensive multicentre study in Turkey investigating MRSA using both epidemiological and genotypic features. The CA-MRSA rate is low in Turkey. Combined use of epidemiological and genotypic methods is the most accurate approach for the diagnosis of CA-MRSA.